The impacts of innovation capability and social adaptability on undergraduates’ employability: The role of self-efficacy - Li, Xiang; Pu, Ruihui; Liao, Hong (Frontiers in Psychology, 2022)
As the world is consistently driven by the infusion of new-generation information technology and the knowledge economy, college students are placed under mounting pressure in developing occupation-related competencies. Their employability has been receiving growing concerns from stakeholders such as higher education institutions, governments, employers, parents, and even student groups themselves as it plays a decisive role in occupational success, social stability, and economic prosperity. Under the theoretical guidance of social cognitive theory, this study set out to investigate the cognitive and psychological mechanisms through which innovation capability, social adaptability, and self-efficacy influence the employability of college students. It also attempts to analyze the mediating role of self-efficacy in the relations between innovation capability, social adaptability, and employability which has been rarely studied in academia. A quantitative approach was employed in this study. Data was collected from 726 undergraduates from 9 higher education institutions in the mainland of China by questionnaire survey method. The research model showed a good fit (χ2/df=4.46, RMSEA=0.069, SRMR=0.049, GFI=0.934, CFI=0.965, NFI=0.955, TLI=0.955). Structural equation modeling (SEM) was applied to this study for data analysis. The findings showed that innovation capability, social adaptability, and self-efficacy significantly and positively correlates with undergraduates’ employability. University students with stronger innovation capability, social adaptability, and self-efficacy tend to be more employable in the job market. Model 4 of SPSS PROCESS Macro revealed that self-efficacy played a mediating role in the correlation between innovation capability, social adaptability, and employability. Undergraduates with higher levels of innovation capability and social adaptability are more confident in their abilities to take specific actions and achieve expected goals, which in turn intensifies their employability. The study suggests the possibility of improving undergraduates’ employability through positive interference of innovation capability, social adaptability, and self-efficacy in the era of information technology and knowledge-based economy.